Study on the influence of environmental regulation on the environmentally friendly behavior of farmers in China - Zhao, Jiajia; Liu, Lingzhi; Qi, Jianling; Dong, Jinpeng (Frontiers in Environmental Science, 2022)
Rural environmental problems have become a prominent problem in the current environmental field that needs to be solved, and livestock breeding waste is an important problem to the rural environmental pollution management. The government has been combating environmental pollution by strengthening environmental regulation policies, but the effect of environmental regulation implementation needs to be improved. Therefore, exploring the intrinsic mechanism of environmental regulation on farmers’ environmental management behavior is an important way to realize the construction of rural civilization. This paper analyzes the influence of environmental regulations on meat duck farmers’ environmentally friendly behavior from the perspective of the “cost effect” and “Porter effect.” In addition, the potential role of risk perception is explored by analyzing the heterogeneity of farmers’ environmentally friendly behavior at different breeding scales. The results show an inverted U-shaped relationship between the intensity of environmental regulations and meat duck farmers’ environmentally friendly behavior; different environmental regulations significantly affect the environmentally friendly behavior of farmers. In these regulations, the guiding regulation plays a significant positive role in the resulting environmentally friendly behavior of farmers in terms of constraint regulation and incentive regulation. There is heterogeneity in the impacts of environmental regulation on the environmentally friendly behaviors of farmers of different scales. Risk cognition has a partial mediating effect on the effects of environmental regulations on farmers’ environmentally friendly behavior. The research not only enriches the study of environmental governance, but also its relevant findings have important guidance and reference significance for optimizing environmental regulation policies, promoting farmers’ cognition of waste environmental pollution management and implementation of environmentally friendly behaviors, and realizing low-carbon and healthy breeding of meat ducks.